Pengendalian Persediaan Bahan Baku Papan Jati Pada Cv. Murah Jaya Meubel Di Kota Kupang - Natalia Desiderata Salu, Antonio E.L. Ny (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2018)
This research aims to investigate the Inventory Control of raw materials on CV. MurahJaya Meubel Kupang City. The research method is descriptive quantitative analyzedusing Economic Order Quantity (EOQ) and Total Inventory Cost (TIC) method. Theresult of this study shows that Economic Order Quantity (EOQ), in 2015 as many as466 sheets, 565 sheets in 2016 and 650 sheets in 2017. The frequency of purchase forthe year 2015 is 7 times, 8 times a in 2016, 9 times a year in 2017. While TotalInventory Cost (TIC) in 2015 is Rp. 1.955,467, in 2016 Rp. 2. 373.544 while in 2017increased by Rp.3.903.231. According to the calculation of Safety Stock in 2015 asmany as 168 sheets, in 2016 as many as 245 sheets and in 2017 as many as 305 sheets.Re-Order Point (ROP) in 2015 as many as 192 sheets, 278 sheets in 2016, and 342sheets in 2017. From this research can be concluded that EOQ method is more efficient.The Total Inventory Cost calculated by EOQ method is lower than the company method.There is a savings on Total Inventory Cost when the company uses EOQ Method in itsRaw Material Inventory.